Evidence The Nexus of Work Discipline and Professionalism on Lecturer Productivity: Study at Private Higher Education Institution - Marilin Kristina; Miswan Miswan; Sudewi Sudewi; Habibah Habibah (eCo-Buss, 2025)
This study aims to investigate the work discipline and professionalism of lecturers and its impact on lecturer productivity, both directly and indirectly, at Private Higher Education Institutions (PHEI). This study used a quantitative approach with the Structural Equation Modeling (SEM) PLS method. Data were obtained from 80 respondents who were lecturers at private universities in Lampung province. The results of the study show that work discipline has a positive and significant effect on lecturer productivity. Additionally, a lecturer's work discipline has a profound impact on professionalism, and professionalism has a significant influence on a lecturer's productivity in private universities. Another important finding is that professionalism plays a significant mediating role in the relationship between work discipline and lecturer productivity in private universities. The main finding of this study confirms that professionalism strengthens the positive impact of work discipline on lecturer productivity in private universities. Implement an objective and transparent performance evaluation system, with indicators that include work discipline, professionalism, and lecturer productivity as a strategy to improve the overall performance of higher education institutions.